EFFECTIVITY TEST OF SIRSAK (Annona muricatal) LEAVES EXTRACT ON DEATH OF AMERICAN KECOA (Periplaneta americana) - Kholila Samosir; Indra Martias; Risman Kurnia; Aurel Syakira; Aurel Syakira (International Journal of Social Science, 2025)
Cockroaches are still the biggest parasite causing health problems in the world. The type of cockroach commonly found in the human environment includes the American cockroach (Periplaneta Americana). One way to control cockroaches is by using vegetable insecticides, such as soursop leaf extract. The purpose of this study was to determine the effectiveness of soursop leaf extract on the death of American cockroaches (Periplaneta Americana). Type of Pre-Experiment Research with research design that is After Only Design. The population and sample of this study used 45 American cockroaches (Periplaneta Americana). The results of soursop leaf extract treatment of American cockroaches (Periplaneta Americana) with a concentration of 20% obtained the number of cockroach deaths as many as 15 tails, then 25% concentration obtained the number of cockroach deaths as many as 15 tails, and 30% obtained the number of deaths as many as 15 tails in 3 different treatments. The conclusion of this study on the death of American cockroaches (Periplaneta Americana) using extracts with the most effective time for the death of American cockroaches (Periplaneta Americana) occurred at 8 o'clock, at 10 o'clock, and at 12 o'clock. Suggestions in this study are to be able to utilize soursop leaf extract as a natural insecticide that is more environmentally friendly and to further research can conduct further research to find more effective concentrations of soursop leaf extract